Deskripsi Tingkat Kesesuaian Persepsi Guru dan Pengalaman Siswa Tentang Penyebab Kesulitan Belajar Matematika Pada Kelas X SMA Negeri Kota Rantepao - Suri Toding Lembang (Jurnal Keguruan dan Ilmu Pendidikan, 2017)
Difficulty learning math can be experienced by students of any ability level or among any group. Mathematics learning difficulties also happens to high school students in the city of Rantepao. With the students 'mathematics learning difficulties, the question arises why this could happen and as educators how teachers' perceptions about mathematics learning difficulties. The teacher is seen as the party that can provide information based on their knowledge and experience in understanding the conditions that may be the cause of timbunya difficulties experienced by students in learning mathematics. Students themselves as parties who have difficulty learning mathematics, is expected to provide information on matters which cause learning difficulties they are experiencing. Therefore the arises the question of how mathematics teachers 'perceptions of the difficulty of learning mathematics class X SMA Negeri City Rantepao?, How difficulty learning mathematics class X SMA Negeri City Rantepao?, And how the level of teachers' perceptions of the difficulty of Conformity math class X SMA Negeri The City of Rantepao?. The purpose of this study was to describe the level of teachers' perceptions of the suitability of mathematics learning difficulties of students on the material in high school trigonometry City State Rantepao. This study used a qualitative descriptive approach-explanative with non-test data collection techniques through an open questionnaire and interviuw, and testing through diagnostic tests. The results showed that: the level of teachers' perceptions of the suitability of mathematics learning difficulties of students in trigonometry material said to be less appropriate. Teachers dominant cause of psychological states and cause epistimolgis, while psychological causes students, epistemological and pedagogical mathematics is the cause of learning difficulties.